(2x-3y)
![(2x - 3y)3 (2x - 3y)3](https://tex.z-dn.net/?f=%282x+-+3y%293)
Answers
Answered by
0
Answer:
8x³+27y³-36x²y-54xy²
Step-by-step explanation:
(a-b)³=a³+b³-3a²b-3ab²
Answered by
1
Step-by-step explanation:
(2x-3y) ( 2x - 3y) ^ 3
= (2x-3y) ( 8 x^3 + 27 y^3 - 3 × 4x ^2 ×3y - 3 × 2x × 9 y^2 )
= (2x-3y) ( 8x^3 + 27 y^3 -36 x^2 y - 54 x y ^2 )
= ( 8x^3 × 2x + 27 y^3 × 2x -36 x^2 y× 2x - 54 x y ^2× 2x )- ( 8x^3 × 3y + 27 y^3 × 3y -36 x^2 y× 3y - 54 x y ^2× 3y )
= 16 x^4+ 54 y^3 x -72x^3 y- 108 x^2 y^ 2 ) -. ( 24 x^3 y+ 81 y^4 -108 x^2 y^2 - 162 x y ^3 )
= 16 x^4+ 54 y^3 x -72x^3 y- 108 x^2 y^ 2- 24 x^3 y- 81 y^4 +108 x^2 y^2 +162 x y ^3
Similar questions
Math,
5 months ago
Math,
5 months ago
Math,
10 months ago
Computer Science,
10 months ago
Science,
1 year ago